Pengaruh Kepuasan dan Kepercayaan Terhadap Loyalitas Mahasiswa dalam Menggunakan Sim Card Prabayar Kartu Tri ‘3’ - Fransiska Madai; Rose Rahmidani (Jurnal Salingka Nagari, 2022)
This study aims to determine the influence of satisfaction and trust on the loyalty of Universitas Negeri Padang students in using the Tri'3' prepaid Sim Card. This type of research is descriptive. The population in this study are the student in Universitas Negeri Padang. The samples are 97 respondents. The sampling technique is purposive sampling technique. The type of data used in this study is primary data that was collected by using questionnaire. The data analysis technique used is multiple regression techniques using the SPSS version 21 program. The results of this study show that: 1) customer satisfaction has a significant effect on the loyalty of Universitas Negeri Padang students in using Tri'3' prepaid Sim Card , 2) trust has a significant effect on universitas Negeri padang student loyalty in using Tri'3' prepaid Sim Card.